14 A systematic review and quality assessment of systematic reviews on ankle sprain injury prevention and treatment. (12th October 2015) - Holden, S; Delahunt, E; Doherty, C
Abstract : Background: Ankle sprains are a prevalent musculoskeletal injury with a high risk of recurrence. This poses significant concern for both population health and athletic performance. Consequently, there is a significant amount of research examining strategies for treating and preventing acute and recurrent sprains. Several systematic reviews evaluating the efficaciousness of numerous different approaches have been undertaken. A single systematic appraisal of the evidence from these reviews is needed to consolidate the current literature and provide appropriate evidence-based guidelines for clinicians. Objective: To evaluate and surmise the evidence from systematic reviews on interventions for preventing and treating acute/recurring ankle sprain injury. Design: Systematic review. Setting: Not applicable. Participants: People with an acute/recurrent ankle sprains. Interventions: Not applicable. Main outcome measurements: Review quality was evaluated using the AMSTAR quality assessment tool. The primary outcomes of interest were injury/re-injury incidence, pain, swelling and function. Results: Forty-five review papers (which themselves contained 307 separate reports) were included in this systematic review of reviews. The included reviews had a mean score of 7/11 on the AMSTAR quality assessment tool. There is strong evidence for bracing and moderate evidence for neuromuscular training in preventing recurrence of an ankle sprain injury. For the combined outcomes of pain, swelling and function after an acute sprain there is strong evidence for non-steroidal anti-inflammatory drugs and early mobilisation, with moderate evidence supporting neuromuscular training and manual therapy techniques. The efficacy of surgery and acupuncture are controversial in the treatment of acute ankle sprains. There is insufficient evidence to support the use of ultrasound in the treatment of acute ankle sprains. Conclusions: This review surmises the evidence base for a number of interventions designed to treat and prevent acute ankle sprain and ankle sprain recurrence. This can guide clinicians to appropriate evidence based practice in the prevention and management of ankle sprain injuries.